Novel Approach to French Fries: Food Products from Potato and Rice Extruded; [Nova Abordagem Para as Batatas Fritas: Produtos Alimenticios a Partir Da Batata E O Arroz Extrudidos]; [Nuevo Enfoque Para Las Papas Fritas: Productos Alimenticios a Partir de la Papa y el Arroz Extruidos] - Monasterio-Aranda, A (Institute of Advanced Studies, University of Santiago de Chile, 2024)
This study aimed to craft an extruded product resembling conventional French fries, utilizing rice as the primary ingredient, and incorporating potato blends to enhance physicochemical and sensory attributes during frying. Mashed potatoes, rice flour, and additives were processed using a twin-screw extruder, followed by frying at 160 °C for 2.15 minutes in three stages. In stage I, four formulations were assessed, with the formulation comprising 70% mashed potato, 30% rice flour, and 0.1% salt displaying superior acceptability and minimal oil absorption (8%). Stage II compared vacuum application to non-vacuum conditions, revealing enhanced sensory acceptability with vacuum due to improved texture and firmness. Combining optimal conditions, stage III yielded the best formulation of 70% mashed potatoes, 30% rice flour, 0.1% salt, and 48% moisture. Extrusion conditions result in heightened sensory evaluation across sensorial parameters. This study pioneers a novel avenue for producing healthier rice-based French fry alternatives via extrusion technology, ameliorating frying attributes. © 2024 Institute of Advanced Studies, University of Santiago de Chile. All rights reserved.